The Importance of Appropriate Parenting Patterns at the Adolescent Development Stage - Silvianetri, Silvianetri; Yeni, Putri; Setianti, Risa Apriliana Desi (Darussalam: Journal of Psychology and Educational, 2024)
Adolescence is an important phase in human development in which individuals experience significant physical, emotional, and social changes. The parenting style applied to teenagers has a crucial role in shaping their independence. This research aims to explore the parenting styles needed to support adolescent development. Adolescent development involves the search for self-identity, exploration of values, and the formation of more complex social relationships. The right parenting style can provide a strong foundation for teenagers in facing these challenges. The required parenting style includes several important aspects. The parenting style needed to support the development of adolescent independence includes clear boundaries, emotional support, opportunities to develop independence, and open communication. A parenting style that pays attention to these aspects will help teenagers build independence, self-confidence and the ability to face the future well.